Recommendations for (Discontinuation of) Statin Treatment in Older Adults: Review of Guidelines. Issue 2 (30th October 2019) - van der Ploeg, Milly A.; Floriani, Carmen; Achterberg, Wilco P.; Bogaerts, Jonathan M.K.; Gussekloo, Jacobijn; Mooijaart, Simon P.; Streit, Sven; Poortvliet, Rosalinde K.E.; Drewes, Yvonne M.
Abstract : OBJECTIVES: As a person's age increases and his/her health status declines, new challenges arise that may lead physicians to consider deprescribing statins. We aimed to provide insight into recommendations available in international cardiovascular disease prevention guidelines regarding discontinuation of statin treatment applicable to older adults. DESIGN: We systematically searched PubMed, EMBASE, EMCARE, and the websites of guideline development organizations and online guideline repositories for cardiovascular disease prevention guidelines aimed at the general population. We selected all guidelines with recommendations (instructions and suggestions) on discontinuation of statin treatment applicable to older adults, published between January 2009 and April 2019. In addition, we performed a synthesis of information from all other recommendations for older adults regarding statin treatment. Methodological quality of the included guidelines was appraised using the appraisal of guidelines for research & evaluation II (AGREE II) instrument. RESULTS: Eighteen international guidelines for cardiovascular disease prevention in the general adult population provided recommendations for statin discontinuation that were applicable to older adults. We identified three groups of instructions for statin discontinuation related to statin intolerance, and none was specifically aimed at older adults. Three guidelines also included suggestions to consider statin discontinuation in patients with poor health status. Of the 18 guidelines included, 16 made recommendations regarding statin treatment in older adults, although details on how to implement these recommendations in practice were not provided. CONCLUSION: Current international cardiovascular disease prevention guidelines provide little specific guidance for physicians who are considering statin discontinuation in older adults in the context of declining health status and short life expectancy. J Am Geriatr Soc 68:417–425, 2020